GC-MS Analysis, Gastroprotective and In Silico Docking Studies of Phytoconstituents from Ixora Javanica Flowers: Pharmaceutical Sciences-Pharmacology for Drug Discovery - Raju, M Ganga; K, Anusha; Suvarchala Reddy, N V L; S, Gayathri; K, Nikitha (International Journal of Life Science and Pharma Research, 2021)
Ixora javanica belongs to the family Rubiaceae having phytoconstituents that are useful in the treatment of various diseases. In our study, the methanolic extract of Ixora javanica flowers was screened for its antiulcer activity. The extract was analyzed using GC-MS to identify significant active constituents, and these constituents were subjected to molecular docking to study their affinity towards the H+/K+ ATPase enzyme. The dry powder of the Ixora javanica flowers was extracted by methanol as the solvent for the soxhlation technique. The extract was then subjected to the GC-MS examination. The in-vivo antiulcer activity was screened using ethanol, indomethacin in pylorus ligation induced gastric ulcer models. The pharmacological evaluation of the extract was carried out using 200 and 400 mg/kg bd. wt. Omeprazole (20 mg/kg, bd.wt, p.o) was used as the standard. Ulcer scores were calculated. Glide 5.6 (Schrodinger Inc.) was used for generating docking simulation studies. The various phytochemical constituents identified from GC-MS study were formononetin, ferulic acid, quinic acid, palmitic acid, oleanolic acid and maslinic acid in higher amounts. The extract exhibited a substantial reduction in the ulcer scores in ethanol, indomethacin, and pylorus ligation prompted gastric ulcer prototypes. A decrease in the ulcers might be due to the presence of phytochemical constituents like terpenoids, flavonoids, phenolic acids, glycosides, alkaloids, steroids, saponins, and tannins present in Ixora javanica flowers, which clearly showed that the extract possesses gastroprotective activity. Molecular docking studies confirmed the H+/K+ ATPase inhibitory effect. Among the identified constituents, formononetin, ferulic acid, and rutin have shown the highest docking scores when compared to other compounds.